DEMOGRAPHIC CHARACTERISTICS OF THE TOWN OF TÂRGU OCNA - Constantin V. ŞTREANGĂ (Management Intercultural, 2014)

(untitled)
The article analyses the demographic evolution of an important urban centre from Moldova in the XVIIIth-XIXth centuries and the causes of its decline during the last century. The locality of Târgu Ocna has represented for 300 years the main urban settlement from the Basin of Trotuş, since it was developing relevant economic activities, which attracted major contingent of population. Târgu Ocna remains a small provincial fair (12.000-14.000 inhabitants), in which youngsters were prevailing, after the appearance of the city of Oneşti nearby after 1950. The population of the town was reaching a maximum of 16.000 inhabitants in the year 1992, in the post-revolutionary period, while the industry was performing in normal parameters, at the end of the decade there were starting to feel the first effects of the local industry reorganization, which imposed the appearance of a high number of unemployed persons, many had to leave the settlement because of the lack of jobs.